UJI AKTIVITAS ANTIOKSIDAN TUMBUHAN Cynara scolimus L., Artemisia china L., Borreria repensDC.,Polygala paniculata L. HASIL KOLEKSI DARI TAMAN NASIONAL GUNUNG MERAPI DENGAN METODE PENANGKAPAN RADIKAL DPPH (2,2-DIFENIL-1-PIKRILHIDRAZIL) - Paulus Eko Murwanto; Djoko Santosa (Faculty of Pharmacy, Universitas Gadjah Mada, 2012)
Taman Nasional Gunung Merapi (TNGM) has various biodiversities which need to be explored. This study aims to analyze antioxidant activity four plants from Asteraceae, Rubiaceae and Polygalaceae which were collected from TNGM. Antioxidant activity is analyzed by DPPH radical capturing method using spectrophotometer. Sampel is extracted gradually by wasbenzen and methanol. DPPH radical capturing analysis shows that IC50 score of Cynara scolimus L. wasbenzen extract is 496,16g/mL; Artemisia china L. 407,86g/mL; Borreria repens DC. 984,04 g/mL and Polygala paniculata L. 633,34 g/mL. The IC50 score of methanol extract Cynara scolimus L. is 334,94g/mL; Artemisia china L. 199,99g/mL; Borreria repens DC. 402,28 g/mL and Polygala paniculata L. 77,00 g/mL . Thin layer chromatography analysis shows that methanol extract of Polygala paniculata L. contains flavonoid.